2017
DOI: 10.7554/elife.29538
|View full text |Cite
|
Sign up to set email alerts
|

Stress responsive miR-31 is a major modulator of mouse intestinal stem cells during regeneration and tumorigenesis

Abstract: Intestinal regeneration and tumorigenesis are believed to be driven by intestinal stem cells (ISCs). Elucidating mechanisms underlying ISC activation during regeneration and tumorigenesis can help uncover the underlying principles of intestinal homeostasis and disease including colorectal cancer. Here we show that miR-31 drives ISC proliferation, and protects ISCs against apoptosis, both during homeostasis and regeneration in response to ionizing radiation injury. Furthermore, miR-31 has oncogenic properties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 63 publications
(118 reference statements)
0
53
0
Order By: Relevance
“…Thus, intestinal epithelial miR‐31‐5p expression seems intrinsically linked to colonic inflammation—known to increase the risk of developing CRC. Alternatively, the poor outcome associated with high MIR31 activity may be related to the role of miR‐31‐5p in promoting stem cell expansion . MIR31 positivity may represent stem cell‐like subpopulations inherently resistant to chemotherapy, and LGR5 + positive stem cells were recently found to be critical in the formation and maintenance of CRC liver metastasis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, intestinal epithelial miR‐31‐5p expression seems intrinsically linked to colonic inflammation—known to increase the risk of developing CRC. Alternatively, the poor outcome associated with high MIR31 activity may be related to the role of miR‐31‐5p in promoting stem cell expansion . MIR31 positivity may represent stem cell‐like subpopulations inherently resistant to chemotherapy, and LGR5 + positive stem cells were recently found to be critical in the formation and maintenance of CRC liver metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…showed that MIR31HG , independent of the encoded miR‐31‐5p, promotes tumor development through HIF1A co‐activation . Tian and colleagues demonstrated that miR‐31‐5p acts as a “cell‐autonomous post‐transcriptional regulator of the ISC [intestinal stem cell] niche” and is induced upon tissue damage by facilitating the subsequent expansion of LGR5 + ISCs as to repopulate the intestinal lining …”
Section: Discussionmentioning
confidence: 99%
“…Using combinational computational methods to predict miR-31 target-pathways, one group found a connection specifically between miR-31 and tight junctions in lung epithelium (36). Most recently, Yu et al demonstrated using in vivo knock-in and knock-out models that miR-31 plays a role in regulating intestinal stem cell behavior during regeneration after radiation injury (37). We show that patient cryptderived colonoids in a sterile environment retain the aberration in miR-31 expression present in the tissue of origin, which supports a cellular defect that is intrinsic and not secondary to inflammation or other external signals due to the presence of disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, in CRC cells, LOC554202 has a tumor suppressor role in the activation of specific caspase cleavage cascades, and low expression of LOC554202 was associated with advanced pathologic stage and increased tumor size (32). miR-31 is a widely investigated miRNA and studies have reported controversial conclusions regarding its role in CRC cells (52)(53)(54)(55)(56). These studies suggest that a high expression of this miRNA in cancer does not always result in a decreased tumor growth, including that noted in cases of the oncosuppressors p53 and phosphatase and tensin homolog.…”
Section: Os ---------------------------------------------------------mentioning
confidence: 99%